Utilizing Balinese Pendet Dance Culture as an Inspirational Idea in Creating "Cening Putri Ayu" Clothing - Salsabila, Hana Tasya; Kusumawardani, Hapsari (Corak, 2025)
The design is inspired by the figure of a Balinese Pendet dancing woman, with traditional clothing worn, ranging from sacred colors such as red, gold, black and white, to accessories worn such as bracelets, earrings, necklaces and head accessories. A "Cening Putri Ayu" is a beautiful princess or woman who also has a strong character, is wise, responsible, but still elegant. Which depicts the figure of a female Pendet dancer on the island of Bali. As well as utilizing local wisdom such as Balinese endek woven fabric as the main material for making this clothing collection. These two elements, the Pendet dance and endek woven cloth, are part of the daily life and religious rituals of the Balinese people, and are part of the cultural heritage that is valued and preserved. Through innovation in creating the "Cening Putri Ayu" clothing, the author presents this clothing at shows and fashion exhibitions. The aim of creating this work is to realize an idea through a fashion collection by highlighting the Balinese Pendet Dance culture as the idea for creating the work "Putri Cening Ayu". The method used is the creation of fashion works which includes three stages, including: (1) Exploration, (2) Design, and (3) embodiment. The results of the creation of this fashion collection produced 2 fashion works "Cening Putri Ayu" which depict the figure of a female Pendet dancer on the island of Bali, namely a beautiful princess or woman who also has a strong, wise, responsible, but still elegant character.ABSTRAKDesain yang terinspirasi dari sosok wanita penari Pendet Bali, dengan pakaian adat yang dikenakan, mulai dari warna sakralnya, seperti merah, gold, hitam, dan putih, hingga aksesori yang dikenakan seperti gelang, anting, kalung dan aksesori kepala. Seorang “Cening Putri Ayu” yaitu putri atau wanita yang cantik juga memiliki karakter kuat, bijaksana, tanggung jawab, tetapi tetap elegan yang menggambarkan sosok wanita penari Pendet di Pulau Bali, serta memanfaatkan salah satu kearifan lokalnya, seperti kain tenun endek Bali sebagai bahan utama pembuatan koleksi busana ini. Kedua unsur ini, tari Pendet dan kain tenun endek, menjadi bagian dari kehidupan sehari-hari dan ritual keagamaan masyarakat Bali, serta menjadi bagian dari warisan budaya yang dihargai dan dilestarikan. Melalui inovasi dalam penciptaan busana "Cening Putri Ayu", busana ini disajikan pada pagelaran show dan pameran busana. Tujuan dari penciptaan karya ini adalah merealisasikan sebuah ide melalui sebuah koleksi busana dengan mengangkat budaya Tari Pendet Bali sebagai ide penciptaan karya "Putri Cening Ayu". Metode yang digunakan adalah penciptaan karya busana meliputi tiga tahapan, di antaranya: (1) Eksplorasi, (2) Perancangan, dan (3) Perwujudan. Hasil penciptaan koleksi busana ini menghasilkan dua karya busana "Cening Putri Ayu" yang menggambarkan sosok wanita penari Pendet di Pulau Bali, yaitu putri atau wanita yang cantik juga memiliki karakter kuat, bijaksana, tanggung jawab, tetapi tetap elegan.